Uropathogenic Escherichia coli infection: innate immune disorder, bladder damage, and Tailin Fang II - Li, Zong-ping; Li, Jun; Li, Tong-lu; Song, Zhi-yong; Gong, Xue-zhong (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Uropathogenic Escherichia coli (UPEC) activates innate immune response upon invading the urinary tract, whereas UPEC can also enter bladder epithelial cells (BECs) through interactions with fusiform vesicles on cell surfaces and subsequently escape from the vesicles into the cytoplasm to establish intracellular bacterial communities, finally evading the host immune system and leading to recurrent urinary tract infection (RUTI). Tailin Fang II (TLF-II) is a Chinese herbal formulation composed of botanicals that has been clinically proven to be effective in treating urinary tract infection (UTI). However, the underlying therapeutic mechanisms remain poorly understood.Methods: Network pharmacology analysis of TLF-II was conducted. Female Balb/C mice were transurethrally inoculated with UPEC CFT073 strain to establish the UTI mouse model. Levofloxacin was used as a positive control. Mice were randomly divided into four groups: negative control, UTI, TLF-II, and levofloxacin. Histopathological changes in bladder tissues were assessed by evaluating the bladder organ index and performing hematoxylin-eosin staining. The bacterial load in the bladder tissue and urine sample of mice was quantified. Activation of the TLR4-NF-κB pathway was investigated through immunohistochemistry and western blotting. The urinary levels of interleukin (IL)-1β and IL-6 and urine leukocyte counts were monitored. We also determined the protein expressions of markers associated with fusiform vesicles, Rab27b and Galectin-3, and levels of the phosphate transporter protein SLC20A1. Co-localization of Rab27b and SLC20A1 with CFT073 was examined using confocal fluorescence microscopy.Results: Network pharmacology analysis suggested that TLF-II could against UTI through multiple targets and pathways associated with innate immunity and inflammation. TLF-II significantly attenuated UPEC-induced bladder injury and reduced the bladder bacterial load. Meanwhile, TLF-II inhibited the expression of TLR4 and NF-κB on BECs and decreased the urine levels of IL-1β and IL-6 and urine leukocyte counts. TLF-II reduced SLC20A1 and Galectin-3 expressions and increased Rab27b expression. The co-localization of SLC20A1 and Rab27b with CFT073 was significantly reduced in the TLF-II group. Conclusions: Innate immunity and bacterial escape from fusiform vesicles play important roles in UPEC-induced bladder infections. Our findings suggest that TLF-II combats UPEC-induced bladder infections by effectively mitigating bladder inflammation and preventing bacterial escape from fusiform vesicles into the cytoplasm.